Increased Macrolide Resistance Rate of M3562 Mycoplasma pneumoniae Correlated With Macrolide Usage and Genotype Shifting - Wang, Yacui; Xu, Baoping; Wu, Xirong; Yin, Qingqin; Wang, Yi; Li, Jieqiong; Jiao, Weiwei; Quan, Shuting; Sun, Lin; Wang, Yonghong; Shen, Adong (Frontiers in Cellular and Infection Microbiology, 2021)
To characterize Mycoplasma pneumoniae (MP) strains and to clarity continuous high rates of macrolide resistance, 1524 oropharyngeal swabs collected from children infected with MP in Beijing Children’s Hospital during 2016-2019 were analyzed. Among 1524 samples, 1386 harbored mutations associated with macrolide resistance; 1049 samples were successfully classified into 11 genotypes using multiple locus variable number tandem repeat analysis (MLVA). The predominant type M4572 decreased from 84.49 to 70.77%, while M3562 increased from 11.63 to 24.67%. Notably, we also found that M3562 with macrolide-resistance drastically increased from 60 to 93.48%. Clinical data suggested that the percentage of resistance with M3562 was higher in macrolide usage group than that of non-drug usage group (90.73 vs 53.57%, P=0.000), while the resistance rate of M4572 was hardly affected by previous macrolide exposure. These findings validated that antimicrobial application and clonal expansion of resistant MP strains play an important role in high rates of macrolide resistant.